Determination of trinitrotoluene at ex-situ prepared bismuth film electrode: An initial study - Sopha, Hanna; Švancara, Ivan (University of Pardubice, 2014)
A bismuth film electrode prepared ex-situ on a glassy carbon powder substrate (BiF-GCPE) was applied to the determination of trinitrotoluene (TNT) in combination with square-wave adsorptive stripping voltammetry. The electroanalytical performance of the BiF-GCPE was studied in Britton-Robinson buffers in the range of pH 4-9, revealing the most favourable stripping signals in mild alkaline solutions (pH 9.0). For calibration, linear responses could be obtained in the concentration range of 0.5-5.0 ppm TNT, when using a deposition time of 60 s (R2 = 0.9999), and within 0.1-1.5 ppm TNT after deposition for 120 s (R2 = 0.9983). The LOD (3F) was estimated to be about 7 ppb (for deposition time of 240 s), and the BiF-GCPE exhibited a very good repeatability (RSD = ±2.3 %; n = 10, ci = 0.5 ppm). Finally, possible determination of TNT in the presence of nitrobenzene was also shown.